Testing the Citizen-Candidate Model - Dan Usher (Queen's University, Department of Economics, 2003)
Citizen-candidate models of representative government postulate that any citizen may become a candidate for office, that a winner is chosen from among the candidates by voting with ties broken by the flip of a coin, that all voters have preferences among a set of policies and that the office-holder adopts his preferred policy. It has been proved on certain assumptions that there exists an equilibrium in these models and that the equilibrium is efficient. The significance of the proof is tested here with reference to the paradox of voting , the exploitation problem and the transposition of the Nash equilibrium from markets to politics. The quest for a political equilibrium leads in the end to the recognition of minimal rock-bottom requirement for cooperation and negotiation in democratic government.
Keywords: H21; 330; Voting; Citizen-Candidate; Efficiency